Physiological toolkit to assess the health impacts on a Magellanic Penguin Spheniscus Magellanicus colony in a high-use touristic region of Patagonia, Argentina - D'Amico, Verónica L. (2019)
We evaluated the health status of Magellanic Penguins Spheniscus magellanicus inhabiting a region on the Valdes Peninsula (Patagonia, Argentina) that is subject to extensive tourism. We compared individuals nesting along tour trails with others inhabiting non-touristic zones. Hematocrits, blood cell counts, glucose, cholesterol, total proteins, and heterophil/lymphocyte were considered as stress indices. Most parameters were not affected by tourism. Adults and chicks tested positive for bacterial pathogens in both the touristic and control areas. These data complemented a long-term database of systematic physiological monitoring on penguins and will be useful tools for future comparative analyses.